Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1007/s00421-012-2346-4
|View full text |Cite
|
Sign up to set email alerts
|

Divergent muscle functional and architectural responses to two successive high intensity resistance exercise sessions in competitive weightlifters and resistance trained adults

Abstract: Peak force (PF), contractile rate of force development (RFD) and contractile impulse (CI) are of great importance to competitive weightlifters (WL). These athletes routinely perform successive bouts of high-intensity resistance exercise (HIRE) within the same day (double-day training) with the aim of improving muscular function and weightlifting performance. The purpose of this investigation was to determine and compare the PF, contractile RFD and CI responses to double-day training between WL and resistance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
0
9
0
1
Order By: Relevance
“…Reliability of the isometric squat test was rated fair in one study [41] and good in three studies [42–44]. Reliability of the isometric leg press was evaluated in one study [45] rated as poor methodological quality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Reliability of the isometric squat test was rated fair in one study [41] and good in three studies [42–44]. Reliability of the isometric leg press was evaluated in one study [45] rated as poor methodological quality.…”
Section: Resultsmentioning
confidence: 99%
“…Ratings for the isometric squat test of fair [41] and good [43] methodological quality were found within the included studies. All four studies performed hypothesis testing with one study additionally investigating construct validity for known positional groups in rugby union players [54].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown a link between fascicle length or fascicle angle and muscle power [14,21,28,42,43], while other studies failed to reveal similar results [28,44,45]. This discrepancy might be due to the differential effect of muscle architecture in the early and late RFD.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio of inclusion of sport-specific training (e.g., sprint training) and resistance training during daily competitive activities may depend on coaches and competitive levels, which might be associated with the discrepancy. In fact, the top level of competitive weightlifters, who frequently include resistance training in their training activities, had a greater VL pennation angle than resistance-trained subjects with a similar VL muscle thickness between the two groups 39) . With respect to the pennation angle, Kawakami et al 10) showed that bodybuilders had a much larger pennation angle (mean, 33°, range 15° to 55°) of TB compared to untrained control subjects (mean, 15°).…”
Section: Andmentioning
confidence: 99%